The Impact of Hospitalization on Psychophysical Development and Everyday Activities in Children (Annual of the Faculty of Philosophy in Skopje, 2018)
Hospitalization plays an important role in the care for children’s health, especiallychildren that require intensive medical care. In comparison to adults, as a result of the insufficient emotional and cognitive maturation on the one hand and the lack of sufficientand appropriate information on the other side, children are significantly more influencedby hospitalization and its associated factors. In addition to having to face the normal developmental lawfulness, hospitalized children also have to face the challenges of separationfrom their home and family, hospitalization, illnesses and clinical procedures that they willundertake.The intensity and the type of the psychosocial reaction of children to the hospitalization depends on significant variables such as the child's age, gender, personality traits,type and severity of the illness, type of treatment, duration of the inpatient length of stayand the time organization in the hospital. The hospitalization usually has a negative impacton the motor, cognitive, emotional and social development of the child.Most negative experiences of hospitalization are due to poor attention to the developmental needs of children in health care planning in hospitals and bad organization of theleisure time.
Keywords: HOSPITALIZATION; PSYCHOPHYSICAL DEVELOPMENT; NEGATIVE EFFECTS; PLAY; EDUCATION